Six years of spreading BLSD skills in schools: empowering teachers as trainers - Calicchia, Sara; Capanna, Silvia; De Rosa, Mariangela; Papaleo, Bruno; Pera, Alessandra (Frontiers in Public Health, 2024)
Introduction To increase the population's ability to handle emergencies, life-saving maneuvers should be universally acquired as an automatic skill starting from school through frequent and practical retraining. Teachers could be ideal multipliers, but it is necessary to design pathways that train and motivate them, since Basic Life Support and Defibrillation (BLSD) skills are not part of their academic curricula. This study explores innovative training solutions and facilitating factors to enhance BLSD education in schools by focusing on the training and motivation of teachers. Methods In the 1st year, an in-service training program for teachers was provided and assessed in a lower middle school in central Italy. The study compared the skills of a group of students trained by teachers with those trained by certified instructors, immediately after the course and 6 months later. Both the procedural skills and the quality of cardiopulmonary resuscitation (CPR) were evaluated, through a hands-on simulation. Over the next 5 years, the project was expanded to three more schools, and a field study was conducted where researchers monitored the teachers in their classroom work, supporting them in resolving critical issues. Results Quantitative assessments showed significant differences in student abilities immediately after the course, which diminished after 6 months. Qualitative evaluations indicated that teachers, initially reluctant, gained confidence and effectively taught BLSD skills. Over 5 academic years, the project expanded to additional schools, training 5,661 students in life-saving maneuvers with a ratio of 1 teacher for every 111 trained students, over the whole period of time. Sustainability factors included regular retraining of teachers, continually updated and free didactic materials and equipment, internal coordinators, allowing teachers the freedom to structure a customized course schedule in terms of timing and delivery methods. Conclusion The study highlights the effectiveness of trained teachers as BLSD knowledge multipliers. Standardizing teacher training, including follow-up retraining, is crucial, but flexibility in student training is beneficial, allowing adaptation to the specific needs of schools. Future research should focus on the long-term sustainability of chain training in larger areas, identifying strategies to overcome organizational and motivational barriers.